Serum Level Profile and Pharmacokinetic Parameters of Single Oral Dose of Metronidazole in Type II Diabetic Patients - A. Kurji, Hayder; M. Ghareeb, Mowafaq; H. Zalzala, Munaf (Iraqi Journal of Pharmaceutical Sciences, 2017)
Many pathophysiological processes can affect the pharmacokinetic properties of drugs in people with diabetes. The present study was deigned to evaluate the influence of diabetes mellitus (DM) on the pharmacokinetic parameters of metronidazole administered as single oral dose. Twelve healthy volunteers and twelve diabetic patients were enrolled in the present study. On day 1, a single oral dose of metronidazole 500 mg was administered orally to all participants at 9:00 am after a 10-hour fasting. Over the following 48 hours, blood samples were taken at frequent intervals and serum metronidazole concentrations were measured by a high-performance liquid chromatography method for assessment of pharmacokinetics of metronidazole. The data indicated that maximum serum concentration (Cmax) and Kelim were significantly decreased (P<0.05) in diabetic patients compared with that reported in healthy subjects (25.73% and 31.51% respectively). Meanwhile, the values of time to reach maximum peak (Tmax), AUClast, AUCtotal, and half life (TÂ½) were significantly increased (P<0.05) compared with those reported in healthy subjects (20.69%, 33.65%, 30.13%, and 20.689% respectively). In conclusion, diabetes mellitus affects some of the pharmacokinetics values of orally administered metronidazole. Key words: Diabetes mellitus , Metronidazole, Pharmacokinetic, Serum Level